Factors Associated with Handwash Behavior in Elementary School Students Medan Sunggal - Nadya Ulfa Tanjung; Ayu Soraya; Sri Wahyuni (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2021)
School-age children are an asset in the future that need to be maintained in improving and protecting health. School-age children, an age group that is vulnerable to health problems because they are in a school environment, are a source of transmission of diseases related to PHBS, especially Hand Washing with Soap (CTPS) is one of the indicators of PHBS in educational institutions. The general objective of the study was to determine the factors related to the behavior of washing hands with soap in State Elementary School Students 060916 Medan Sunggal. This type of research is quantitative with a cross sectional approach. The total population in the study conducted was 301 students, with a sample of 70 respondents. The research sample was taken using a non-random sampling technique, namely purposive sampling. The results of univariate and bivariate analysis used statistical tests and chi square tests (significant level 0.05). The results showed as many as 35.7% of respondents had good hand washing behavior with soap. Furthermore, from the results of the study, it was found that there was no relationship between knowledge (P-value = 0.083) and the behavior of washing hands with soap and there was a relationship between habits (P-value = 0.000) and the behavior of washing hands with soap. Meanwhile, the variables of facilities and infrastructure and teacher support are no longer analyzed for bivariate analysis, because the respondents' answers are homogeneous. From the results of this study, the conclusions obtained are that there is no relationship between knowledge and hand soap, there is a relationship between habits and behavior of washing hands with soap, facilities and infrastructure, teacher support, the answers of the respondents are homogeneous. Suggestions from this study are that students can increase awareness and behavior of washing hands with soap properly.